SOCIAL CONSTRUCTION AND THE ROLE OF CHINESE TEMPLE IN ELIMINATING CHINESE ETHNIC PREJUDICE (Study of Local Wisdom in Semarang Chinatown) - Atmaja, Hamdan Tri; Ba’in (International Journal of Psychosocial Rehabilitation, 2020)
The harmonious relationship of indigenous people and Chinese people was somewhat disturbed in the political year. It was marked by the emergence of the issue of ethnic prejudice which was used in campaign activities. Meanwhile, Chinese Temple as the symbol of Chinese identity has never been disturbed and it has almost never been a source of conflict between indigenous people and Chinese people.This uniqueness encourages the writer to conduct a study of how social construction of Chinese temple and the role of Chinese Temple in eliminating Chinese ethnic prejudice. The method used in this study was qualitative method with phenomenological approach. The result of the study showed that the social construction of Chinese Temple can be grouped into three. The first group constructs the Chinese Temple as the religious building. The second group constructs the Chinese Temple as the unique building to be developed as a tourist attraction. The third group constructs the Chinese Temple as a historic building that must be recognized as part of Indonesian culture. The role of Chinese Temple can be a medium of inter-ethnic communication which not only unite the various interests of different social strata but also eliminate the ethnic prejudice. This study recommends that it is necessary to socialize the cultural perspective rather than political perspectives for the people towards the Chinese. Because cultural perspectives will lead to similarity whereas political perspectives will lead to diversity.